2021
DOI: 10.3389/fphys.2020.613367
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in T Cells Is Induced by Binding to Nickel-Chelating Lipids in Supported Lipid Bilayers

Abstract: Supported lipid bilayers (SLBs) are one of the most common cell-membrane model systems to study cell-cell interactions. Nickel-chelating lipids are frequently used to functionalize the SLB with polyhistidine-tagged ligands. We show here that these lipids by themselves can induce calcium signaling in T cells, also when having protein ligands on the SLB. This is important to avoid “false” signaling events in cell studies with SLBs, but also to better understand the molecular mechanisms involved in T-cell signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
4
6
0
Order By: Relevance
“…Interestingly, the 2D affinities measured by Huppa et al were of similar magnitude at 24 and 37 °C (Huppa et al, 2010), a correlation that has also been observed by us for CD4 binding pMHC class II molecules (Jönsson et al, 2016) and for rat CD2 binding rat CD48 T92A (Junghans et al, 2020;Dam et al, 2021). Nonetheless, Huppa et al (2010) observed a monotonic decrease from 1.7 to 0.1 s in 2D lifetimes as the temperature was increased from 24 to 37 °C.…”
Section: Single-molecule Methods To Measure 2d Binding Kineticssupporting
confidence: 81%
See 3 more Smart Citations
“…Interestingly, the 2D affinities measured by Huppa et al were of similar magnitude at 24 and 37 °C (Huppa et al, 2010), a correlation that has also been observed by us for CD4 binding pMHC class II molecules (Jönsson et al, 2016) and for rat CD2 binding rat CD48 T92A (Junghans et al, 2020;Dam et al, 2021). Nonetheless, Huppa et al (2010) observed a monotonic decrease from 1.7 to 0.1 s in 2D lifetimes as the temperature was increased from 24 to 37 °C.…”
Section: Single-molecule Methods To Measure 2d Binding Kineticssupporting
confidence: 81%
“…Care should thus be taken on the state of the T cells when measuring ligand-receptor affinity. This can in particular be a problem when using an SLB containing nickel-chelating lipids that on their own have been shown to induce cell activation unless effectively blocked (Dam et al, 2021). In order to minimize intracellular interactions upon cell activation, it is also possible to take advantage of protein design, for example by only expressing the extracellular region of the studied receptor on the cell surface (Junghans et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apparently, structural features of microvilli favor this segregation. Of particular interest is the piece by Dam et al that discussed a phenomenon related to this topic (5). Supported lipid bilayers are commonly used a surrogate of MHC/peptide to interact with TCR.…”
Section: Editorial On the Research Topic The Role Of Biomembranes And Biophysics In Immune Cell Signalingmentioning
confidence: 99%